The Fate of Dietary Cholesterol in the Kissing Bug Rhodnius prolixus - Entringer, Petter F.; Majerowicz, David; Gondim, Katia C. (Frontiers in Physiology, 2021)
Insects are unable to synthesize cholesterol and depend on the presence of sterols in the diet for cell membrane composition and hormone production. Thus, cholesterol absorption, transport, and metabolism are potencial targets for vector and pest control strategies. Here, we investigate the dietary cholesterol absorption and tissue distribution in the kissing-bug Rhodnius prolixus using radiolabeled cholesterol. Both the anterior and posterior midguts absorbed cholesterol from the ingested blood, although the anterior midgut absorbed more. We also observed esterified cholesterol labeling in the epithelium, indicating that midgut cells can metabolize and store cholesterol. Only a small amount of labeled cholesterol was found in the hemolymph, where it was mainly in the free form and associated with lipophorin. The fat body transiently accumulated cholesterol, showing a labeled cholesterol peak on the fifth day after the blood meal. The ovaries also incorporated cholesterol, but cumulatively. The insects did not absorb almost half of the ingested labelled cholesterol, and radioactivity was present in the feces. After injection of 3H-cholesterol-labeled lipophorin into females, a half-life of 5.5 ± 0.7 h in the hemolymph was determined. Both the fat body and ovaries incorporated lipophorin-associated cholesterol, which was inhibited at low temperature, indicating the participation of active cholesterol transport. These results help describe an unexplored part of R. prolixus lipid metabolism.